2001
DOI: 10.3354/meps222109
|View full text |Cite
|
Sign up to set email alerts
|

Size, survival and the potential for reproduction in transplants of Mazzaella splendens and M. linearis (Rhodophyta)

Abstract: Biomechanical models of red algae have been developed that make predictions about blade survivorship based on tissue strengths, drag coefficients, and blade surface areas. The first 2 objectives of the present field study were therefore to examine actual survivorship of genets (i.e. holdfast + blades) from wide-and narrow-bladed species of Mazzaella G. DeToni f., as well as to compare blade survivorship to predictions of their survival from a previous biomechanics study of the 2 species. The third and fourth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
13
2
Order By: Relevance
“…We found, for example, that 50% of breakage occurred at the stipe-holdfast junction when testing frond strength with this method. However, measurements of waveinduced (not researcher-induced) breakage contradicted initial results, finding that fracture occurred more often in blades than at stipe-holdfast junctions (Shaughnessy and DeWreede, 2001). Thus, model predictions in this study assessed breakage where it often occurs, in frond blades, although other breakage locations are possible in M. flaccida fronds and thalli.…”
Section: Locations Of Breakagecontrasting
confidence: 37%
“…We found, for example, that 50% of breakage occurred at the stipe-holdfast junction when testing frond strength with this method. However, measurements of waveinduced (not researcher-induced) breakage contradicted initial results, finding that fracture occurred more often in blades than at stipe-holdfast junctions (Shaughnessy and DeWreede, 2001). Thus, model predictions in this study assessed breakage where it often occurs, in frond blades, although other breakage locations are possible in M. flaccida fronds and thalli.…”
Section: Locations Of Breakagecontrasting
confidence: 37%
“…Using sequence of the large subunit of rubisco (rbcL), Hommersand et al (1994) were able to establish clearly genetic differences between M. f laccida and M. splendens, but not strongly between two samples of the latter and an isolate of M. linearis included in their study. A series of reciprocal transplant experiments, however, support recognition of M. linearis and M. splendens as distinct species, and indicate that plants of intermediate morphology were exposed variants of the latter (Shaughnessy 1996;Shaughnessy & DeWreede 2001). Ross et al (2003) outlined possible scenarios to explain the apparent morphological continuum observed in the field for the M. linearis/splendens complex: (i) a single species exists with substantial morphological plasticity in response to wave exposure; (ii) two species exist, but one or both display phenotypic plasticity such that the intermediate plants are strictly of one species or the other, or a mixture of plants from both; (iii) the intermediate plants may be tetrasporophytes of M. splendens, which was reported to have a possible heteromorphic aspect to its alternation of generations ; (iv) the intermediates are hybrids between the two species; and (v) combinations of the previous could also explain these individuals.…”
Section: Resultsmentioning
confidence: 99%
“…There are other potential break locations: in stipes, at stipe-holdfast junctions, and at holdfast-substratum interfaces. Although initial examinations of M. splendens, in which investigators folded blades over experimental scale apparatuses and pulled on the macroalgae in the field, suggested breakage occurs primarily at stipe-holdfast junctions (Shaughnessy et al, 1996), subsequent measurements of wave-induced breakage found that fracture occurs within blades more often than at stipe-holdfast junctions (Shaughnessy and DeWreede, 2001). The current study thus evaluates a significant breakage location, the algal blade, but fracture may also happen elsewhere in Mazzaella thalli.…”
Section: Implications For Natural Populationsmentioning
confidence: 92%
“…Holdfast and frond(s) together constitute the seaweed's thallus. Macroalgal breakage assumes a variety of forms, with some species' fronds tattering marginally (Black, 1976;Blanchette, 1997;Dudgeon et al, 1999), other species' thalli breaking in the middle of blades or at holdfast-stipe junctions (Carrington, 1990;Hawes and Smith, 1995;Shaughnessy et al, 1996;Shaughnessy and DeWreede, 2001;Carrington et al, 2001;Johnson, 2001), and still other species commonly dislodging due to holdfast or substratum failure (Black, 1976;Koehl, 1986;Seymour et al, 1989;Utter and Denny, 1996;Gaylord and Denny, 1997). For most seaweeds, such breakage ultimately results in the death of dislodged portions of algal thalli.…”
Section: Introductionmentioning
confidence: 99%